Modélisation, Simulation et commande de la machine synchrone à aimant permanent - محمد حفناوي, دعمش; علي, شراحي; محمد الحبيب, كوت (University of El-Oued, 2021)
"Permanent magnets synchronous machines are considered to be one of the most important induction machines, because in recent years they have experienced a great development and this thanks to the permanent magnet, in particular of the rare earth type, which has known major improvements in terms of quality, as well as the development observed by non-linear control techniques and power electronics, in particular inverters. In this brief, we have presented a detailed study on the MSAP. Then a modulization of the motor in the binary frame based on the transformation of Park. And then the simulation of the motor in the MATLAB program with the use of a regulator-Integral proportional- of speed and current in order to optimize the control of speed and torque. And this is all under vector control. " "تعد الالات التزامنية ذات المغناطيس الدائم من اهم الالات الحثية, حيث شهدت في السنوات الاخير تطورا كبير و هذا بفضل المغناطيس الدائم و خاصة من نوع الاتربة النادرة و التي شهدت تحسينات كبيرة من حيث الجودة, و كذا التطور الذي شهدته تقنيات التحكم الغير خطية و الكترونيات الطاقة و خاصة المحولات. قدمنا في هاته المذكرة دراسة مفصلة عن المحرك التزامني ذو المغناطيس الدائم. و بعدها محاكاة للمحرك في المعلم الثنائي مع الاعتماد على تحويل بارك. و من ثما نمذجة للمحرك في برنامج الماتلاب مع استخدام معدل - تناسبي تكاملي - للسرعة و التيار بغرض التحكم الامثل في السرعة و العزم. و كل هذا ضمن التحكم الشعاعي."
Electromécanique مذكرة ماستر تخصص
Keywords: Key words: Permanent magnet synchronous machine, PWM, Field oriented control, inverter; الكلمات المفتاحية : الالة المتزامنة ذات المغناطيس الدائم, التحكم بتوجیه التدفق, تعدیل عرض النبضة, العاكس